Leguminosas arbóreo-arbustivas como fonte de nutrientes em plantio de coqueiro - Magalhães, Rafaela Batista (2023)
The sustainability of coconut farming can be favored by the management of legumes that provide nutrients to the main crop. The variety of legume species and their planting density depend on soil and climate conditions. In this study, the following hypotheses were tested: 1 The species Mimosa caesalpiniaefolia Benth (M. Caesalpiniaefolia), cultivated in rainfed in sandy soil availability in the region with low water content, develops better and provides more availability (N) and other nutrients to the coconut tree from pruning the biomass of the aerial part when selected to Gliricidia sepium (Jacq) Kunth ex Walp (G. sepium); 2) Lower plant density favors the production of leguminous biomass and greater accumulation of nutrients to make available to coconut trees; 3) N and other nutrients from legume pruning have their availability in the soil increased; 4) N and other nutrients from the pruning of legumes are absorbed by their coconut status, favoring their nutritional status; 5) N and other nutrients accumulated in the environmental biomass of agricultural legumes in the management of coconut trees. The study was carried out in Itarema (CE), with a randomized block design and a 2 x 3 + 1 factorial scheme with four replications. The treatment factors were two legume species (M. caesalpiniaefolia and G. sepium) at three planting densities: low (10,000 plants/ha), medium (20,000 plants/ha), high (40,000 plants/ha) and additional treatment. (regeneration vegetation). Legumes were planted in 2019 and pruned in two cycles (2020 and 2021). The evaluations were: biomass and nutrient accumulation in the pruning biomass; nutrient contents in the soil collected after pruning; nutritional status and fruit weight of coconut trees. Data were submitted to analysis of variance, Tukey's and Dunnet's tests at 5% significance and to multivariate analysis (SAS). In the first cycle, M. caesalpiniaefolia showed higher production of dry biomass at high density (7.6 Mg ha-1), as well as greater accumulation of nutrients, especially C (334 kg ha-1). In the second cycle, G. sepium showed higher production of dry biomass, as well as higher accumulation of nutrients, especially N, K and Mg (673.3, 428.19 and 46.5 and kg ha-1). In the first cycle, G. sepium at medium density impacted the availability of Mg and N in the soil, whose contents were 1.5 and 1.8 g kg-1respectively. The nutritional status of coconut palms and fruit weight were not affected by legumes at planting densities. G. sepium at medium density is more suitable for intercropping with coconut trees in soil and climatic conditions similar to the experimental site. nutrients from legume pruning residues.